Analysis of the Involvement and Role of Women Farmers in Peatland Horticultural Agricultural Development Efforts (Case Study of Horticultural Agricultural Land Belonging to the Maju Jaya Bersama Farmer Group in Kampung Baru Hamlet, Batang Duku Village, Bukit Batu District, Bengkalis Regency, Riau Province) - Tahsa Ayu S; Leonardo Manullang; vina widyaningsih (Prospect Publishing, 2023)
Maju Jaya Bersama Farmer Group is one of the horticultural farming groups assisted by CSR PT Kilang Pertamina Internasional RU II Produksi Sungai Pakning, which has been empowered since 2022, is located in Kampung Baru Hamlet, Batang Duku Village, Bukit Batu District, Bengkalis Regency, Riau Province. The empowerment assistance carried out by the company aims to improve the habits of farmers in agricultural land processing techniques that are not environmentally friendly and to increase the capacity of group members in developing agriculture. Another goal is to encourage the optimization of the application of irrigation management on agricultural land, regulate land spatial planning to strengthen group institutions. The program implemented by the company promotes inclusivity by taking into account the needs and interests of members of women's groups. This effort is carried out through education related to the processing of harvested products and access to marketing as well as empowerment in social and political aspects so that they have the capability to be directly involved and actively participate in group planning and policies. Therefore, this research is focused on analyzing the participation and role of women farmers and the social capital owned by the group in encouraging the sustainability of the community empowerment program initiated by CSR PT Kilang Pertamina Internasional RU II Produksi Sungai Pakning. This study uses a descriptive qualitative approach supported by data collection techniques by snowball sampling. The results of the study show that economic factors are the main reason why female members of the Maju Jaya Bersama Farmer Group join to help meet household needs. They have a significant role in managing agricultural land even though they have a double burden because they still have to work at home. Their active participation in forms, ideas, labor, and decision-making has resulted in changes in land management and management systems that are able to overcome problems within the group. The access of female members to gain knowledge is an important aspect for increasing knowledge and skills so that their role and participation in the group is increasing and sustainable.